Hepatocellular Carcinoma: An Unusual Presentation of this Rare Clinical Entity in Children - Martins, M (2021)
Malignant hepatic tumors are rare in children and hepatocellular carcinomas only represent 20% of cases. A previously healthy 10 year-old male was admitted for sudden abdominal pain. Ultrasound imaging showed an ileo-ileal intussusception with spontaneous resolution, but in the face of worsening pain, fever, and a palpable epigastric mass, abdominal magnetic resonance imaging was performed, showing a liver lesion. Laboratory tests presented elevated liver enzymes and C-reactive protein, so a liver abscess was considered and treated with metronidazole plus ceftriaxone. All of the microbiology tests as well as tumoral markers were negative. Despite clinical and laboratory improvement, the lesion persisted in the imaging. A liver biopsy confirmed a hepatocellular carcinoma, and the patient was submitted to surgical resection and chemotherapy. Contrarily to adults in whom most cases are secondary to chronic liver disease, children may not have risk factors for the disease, which makes it harder to make a prompt diagnosis.